2002
DOI: 10.1046/j.1365-2958.2002.03091.x
|View full text |Cite
|
Sign up to set email alerts
|

Imp/OstA is required for cell envelope biogenesis in Escherichia coli

Abstract: SummaryIn Gram-negative bacteria, all components of the outer membrane are synthesized in the cytoplasm or the cytoplasmic leaflet of the inner membrane and must thus traverse the inner membrane and the periplasm on the way to their final destination. In this study, we show Imp/OstA to have characteristics typical for proteins involved in envelope biogenesis. Imp is essential and forms a high-molecular-weight disulphide-bonded complex in the outer membrane. Upon depletion of Imp, lipids and outer membrane prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
244
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(260 citation statements)
references
References 36 publications
16
244
0
Order By: Relevance
“…This higher density might result from an increased protein to lipid ratio. Consistently, whereas OMP assembly appeared unaffected by Imp depletion, both in E. coli (6) and in N. meningitidis (this study), we have demonstrated now that Imp depletion results in decreased levels of LPS in the OM, thus changing the protein:lipid ratio. Also, the observations that missense mutations in the E. coli imp gene resulted in increased sensitivity to hydrophobic agents (7,8) can now be understood: these mutants likely suffered from reduced levels of LPS, a property known to affect the integrity of the OM (23).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This higher density might result from an increased protein to lipid ratio. Consistently, whereas OMP assembly appeared unaffected by Imp depletion, both in E. coli (6) and in N. meningitidis (this study), we have demonstrated now that Imp depletion results in decreased levels of LPS in the OM, thus changing the protein:lipid ratio. Also, the observations that missense mutations in the E. coli imp gene resulted in increased sensitivity to hydrophobic agents (7,8) can now be understood: these mutants likely suffered from reduced levels of LPS, a property known to affect the integrity of the OM (23).…”
Section: Discussionsupporting
confidence: 87%
“…The desialylation of a small portion of the LPS observed when whole cells of the imp mutant were treated with neuraminidase was mostly likely due to the diminished membrane integrity in these bacteria, which may have been reinforced by the repeated centrifugation and respuspension steps required for this assay. Because Imp itself is an OMP, as shown by its presence in purified Neisserial (this study) and E. coli (6) OMs, Imp is likely the transporter that mediates the f lip-f lop of LPS over the OM, although an additional role in transport through the periplasm cannot be excluded at this stage.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Two of these proteins, LptD and LptE (formerly Imp and RlpB, resp. ), reside in the OM and are responsible for the translocation of LPS across the OM (to the cell surface) in the final stages of assembly (8)(9)(10).…”
mentioning
confidence: 99%